Criminal-Legal, Criminological, and Forensic Aspects of the Public Demonstration of Crimes Against Individuals on the Internet - Yu. S. Pestereva; S. E. Timoshenko (Сибирское юридическое обозрение)
This article examines the criminal-legal, criminological, and forensic characteristics, as well as specific investigative aspects, of “trash streams” – online broadcasts that display the commission of crimes. These streams contain criminologically significant information and promote unlawful behavior, making the actions of individuals involved in such broadcasts subject to criminal and forensic analysis. It is concluded that current criminal law does not establish separate liability for trash streams; within the framework of existing legislation, there has only been an intensification of criminal responsibility for already established crimes against individuals. In attempts to impose specific liability for trash streams, legislators have not adequately addressed the criminal motives of the perpetrators or the role of “viewers” of these streams. However, complicity provisions allow law enforcement to consider these viewers as accomplices or instigators. The Authors argue that in cases of live broadcasting of illegal actions as specified under Articles 105, 111, 112, 117, 119, 126, 127, 1271 , and 1272 of the Criminal Code of the Russian Federation, it is appropriate to consider the context of the crime’s commission. Meanwhile, the broadcast of recordings of these crimes should be treated as criminalized post-crime behavior. In both scenarios, public morality serves as an auxiliary object of this category of crimes.